GE_GERICHTE PM/1509/2011 vom 16. März 2012 - GE Cour de justice (2012)
; DÉFENSE NÉCESSAIRE ; DÉFENSE D'OFFICE ; DÉCISION DE RENVOI ; RESTITUTION DU DÉLAI ; LIBÉRATION CONDITIONNELLE | CPP.130; CPP.131; CPP.132; CPP.409; CPP.94; CP.89